2021
DOI: 10.1007/s11408-021-00386-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in co-movement and risk transmission between South Asian stock markets amidst the development of regional co-operation

Abstract: This paper documents evidence of changes in the co-movement of stock returns and risk transmission among four South Asian stock markets over periods of regional market reform and global market instability. The sample period (1993–2015) is disaggregated into three sub-periods: before and after the establishment of the South Asian Federation of Exchanges (SAFE) and after the 2008 Global Financial Crisis. The principal components investigation and cointegration analysis conclude that the co-movement among stock r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Akter and Nobi (2018) also noted an augmented degree of association during and after crises compared to the periods preceding crises. More recently, Khan et al (2022) found that market integration increased following the GFC. These heightened linkages among markets hold significant implications for both domestic and international investors contemplating these assets for portfolio investments.…”
Section: Resultsmentioning
confidence: 99%
“…Akter and Nobi (2018) also noted an augmented degree of association during and after crises compared to the periods preceding crises. More recently, Khan et al (2022) found that market integration increased following the GFC. These heightened linkages among markets hold significant implications for both domestic and international investors contemplating these assets for portfolio investments.…”
Section: Resultsmentioning
confidence: 99%
“…A global approach is being taken to these studies, as they concentrate on countries outside of trade blocs as well as those with trade blocs (Daelemans et al, 2018). Khan et al (2021), the literature offers benefits and problems associated with business integration (Paramati et al, 2018). More investors see convergence as less as a source of strength and more as a drawback to the goal and simplification of simplifying markets (Ferreira, 2017;Pirzado et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These are the DSE, Bangladesh's newest controversies [ 14 ]. However, the stock market scandal may hurt domestic economic activity and international investors [ 15 ]. It is mentioned that DSE-listed banking and financial companies frequently use CAP.…”
Section: Introductionmentioning
confidence: 99%